2022
DOI: 10.1097/ju.0000000000002120
|View full text |Cite
|
Sign up to set email alerts
|

Systematic versus Targeted Magnetic Resonance Imaging/Ultrasound Fusion Prostate Biopsy among Men with Visible Lesions

Abstract: Purpose: Multiparametric magnetic resonance imaging (mpMRI)-ultrasound (US) fusion-guided biopsy may improve prostate cancer (PCa) detection and reduce grade misclassification. We compared PCa detection rates on systematic, magnetic resonance imaging-targeted, and combined biopsy with evaluation of important subgroups. Materials and Methods: Men with clinical suspicion of harboring PCa from 2 institutions with visible Prostate ImagingeReporting and Data System (PI-RADS TM v2) lesions receiving mpMRI-US fusion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…While the study did not directly compare the effects of PHI combined with PI-RADS, it indirectly illustrated the importance of combining PHI and mpMRI, which indicated that the two indicators can also be beneficial to white and Caucasian populations. A study from Loyola and UAB populations showed that Asian American men have a lower risk of PCa (OR = 0.15, 95% CI: 0.06-0.42) and CSPCa (OR = 0.34, 95% CI: 0.12-1.02) than other races (33). For men with African ancestry, Patel et al conducted a study evaluating implications of race (African American men versus non-African American men) and tumor location for PCa detection (34).…”
Section: Discussionmentioning
confidence: 99%
“…While the study did not directly compare the effects of PHI combined with PI-RADS, it indirectly illustrated the importance of combining PHI and mpMRI, which indicated that the two indicators can also be beneficial to white and Caucasian populations. A study from Loyola and UAB populations showed that Asian American men have a lower risk of PCa (OR = 0.15, 95% CI: 0.06-0.42) and CSPCa (OR = 0.34, 95% CI: 0.12-1.02) than other races (33). For men with African ancestry, Patel et al conducted a study evaluating implications of race (African American men versus non-African American men) and tumor location for PCa detection (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although guidelines on PCa management stratify low risk and veryelow risk groups by volume, oncologic implications of volume have blurred in the MRI era with improved tissue sampling from combined targeted and systematic biopsy, and changes in pathological grading. 3 Future guidelines may place a greater emphasis on imaging, genomics, and emerging tools rather than disease volume for clinically localized PCa.…”
Section: Editorial Commentsmentioning
confidence: 99%
“…Several recent prospective studies support the use of multiparametric (mp)MRI and fusion biopsies to improve detection of clinically significant prostate cancer (csPCa) [ 1 , 2 , 3 ]. Targeted biopsies have been shown to increase detection of csPCa while reducing detection of grade group (GG)1 prostate cancer (PCa) compared to systematic biopsies alone [ 4 , 5 ]. Although it loses the benefit of reduced GG1 PCa detection, the combined biopsy approach of both targeted and systematic biopsies optimizes identification of csPCa and is often employed in clinical practice, as recommended by guidelines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%